ON THE LEXICAL GREECISM IJEREJЬ IN TWO TYPES OF CROATIAN GLAGOLITIC TRANSLATIONS - Zabransky, Lukas (Bohemica Olomucensia, 2020)
Croatian Glagolitic manuscripts represent a very important source not only for the study of translation literature. Many of the Croatian Glagolitic texts constituting the translation literature are based on Greek originals and their roots are thus undoubtedly linked to the Great Moravian literature. A vocabulary of the Croatian Glagolitic texts contains some lexemes, which are classified as archaisms in terms of the classical Old Church Slavonic. These archaisms include, among others, greecisms; among them also the lexeme ijerejь ('priest'). This greecism is surprisingly also a part of the Croatian Glagolitic translations according to the Latin original. In addition to the Croatian Glagolitic translations of Bible verses from the Latin, the lexeme ijerejь / ijerejь is along with its derivatives also documented in Croatian Glagolitic translations of Jan Hus' Interpretation of the Ten Commandments and in the translation of the Jan Hus' text in his homily for the 13th Sunday after Pentecost. Since these are two types of translations with the incidence of the greecism ijerejь / ijerejь - the translation of the biblical text from Latin and the translation of the Old Czech text into the Old Croatian -, whose origins are rather distant both in terms of time and space, it must be assumed that this greecism was not only a part of the idiolect of one translator. Probably it had formed a part of the vocabulary of Croatian Glagolitic monks since the earliest times, perhaps since as early as the period before St. Cyril and Methodius.
Keywords: Jan Hus; Croatian Glagolitic manuscripts; Greecisms; Old Church Slavonic; Church Slavonic; Old Czech; Bible; homily; priest